Promoting a bundle of biofortified seeds and agricultural inputs in northeastern Nigeria - Misra, Rewa S.; Amare, Mulubrhan; Ambler, Kate; Bamiwuye, Temilolu; Bloem, Jeffrey R.; Wagner, Julia (International Food Policy Research Institute, 2023)
Smallholder farmers in northeastern Nigeria face the triple threat of food insecurity, climate volatility, and conflict. Northeastern Nigeria has some of the highest levels of food insecurity in Nigeria. Additionally, delayed, shorter, and more volatile rainy seasons have led to massive floods, depleted soil quality, and disrupted agricultural growing seasons which ultimately constrain agricultural productivity. Moreover, conflict between pastoralist livestock herders and settled agricultural communities over land use, as well as extremism, has led millions of people to flee from their homes.